2014
DOI: 10.1007/s00436-014-4097-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of Parascaris equorum larvae and initial investigation of parasite excretory-secretory products

Abstract: Currently, diagnosis of Parascaris equorum infection in equids is limited to patent infections. The goals of this study were to culture P. equorum larvae in vitro and identify excretory-secretory (ES) products for prepatent diagnostic testing. Parascaris equorum L2/L3 larvae were hatched and cultured for up to 3 weeks for ES product collection. Fifth stage (L5) P. equorum were also cultured for ES product collection. Examination of ES fractions by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…suum worms without CO2 (Weisblat and Russel, 1976;Brownlee et al 1997;Chehayeb et al 2014;McCoy et al 2015). Jansen et al (2013) maintained P. equorum adult worms without 5% CO2 while Burk et al (2014) cultured second and third larval stages of P. equorum under 5% CO2 conditions, but not the adult worms. Based on these reports, it appears that adult worms may not require CO2, but this had not been specifically evaluated for Parascaris spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suum worms without CO2 (Weisblat and Russel, 1976;Brownlee et al 1997;Chehayeb et al 2014;McCoy et al 2015). Jansen et al (2013) maintained P. equorum adult worms without 5% CO2 while Burk et al (2014) cultured second and third larval stages of P. equorum under 5% CO2 conditions, but not the adult worms. Based on these reports, it appears that adult worms may not require CO2, but this had not been specifically evaluated for Parascaris spp.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only two studies have reported the in vitro maintenance of Parascaris spp. Burk et al (2014) reported culturing of larval stages and maintenance of adult stages to investigate the production of excretory-secretory products. In that study, two adult worms were maintained in RPMI-1640 medium at 37˚C for five days.…”
Section: Introductionmentioning
confidence: 99%
“…; Burk et al . ) have not yet led to a validated diagnostic tool similar to that developed for diagnosis of A. suum infection in pigs (Vlaminck et al . ).…”
Section: Diagnostic Techniquesmentioning
confidence: 97%
“…Attempts to evaluate serological responses to Parascaris spp. infection (V€ ollger et al 2012;Burk et al 2014) have not yet led to a validated diagnostic tool similar to that developed for diagnosis of A. suum infection in pigs (Vlaminck et al 2012). Serological diagnosis of Parascaris spp.…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation